Alveolar type II epithelial cells produce interleukin-6 in vitro and in vivo. Regulation by alveolar macrophage secretory products. - B Crestani; P Cornillet; M Dehoux; C Rolland; M Guenounou; M Aubier (The Journal of Clinical Investigation, 1994)
The aims of this study were (a) to determine if rat alveolar type II (ATII) cells and human pulmonary epithelial-derived cells (A549 cell line) could generate IL-6 in vitro, (b) to characterize the cytokine regulation of IL-6 gene and protein expression in these cells, and (c) to detect the in vivo expression of immunoreactive IL-6 by human ATII cells. Rat ATII cells in primary culture secreted bioactive IL-6 and immunostained with an anti-IL-6 antiserum. Spontaneous IL-6 secretion by rat ATII cells amounted to 5,690 +/- 770 pg/ml/10(6) cells (n = 12) and was fivefold higher than spontaneous rat alveolar macrophages IL-6 secretion (1,052 +/- 286 pg/ml/10(6) cells, n = 8, P = 0.001). Rat alveolar macrophage conditioned media (CM) increased IL-6 secretion by rat ATII cells through the effect of IL-1 and TNF. IL-6 gene expression and IL-6 secretion by A549 cells was induced by IL-1 beta, TNF alpha, and by human alveolar macrophages and THP1 cells CM. Induction was abolished when CM were preincubated with anti-IL-1 beta and anti-TNF alpha antibody. The combination of IFN gamma and LPS induced the expression of IL-6 mRNA by A549 cells whereas LPS alone had no effect. Immunohistochemical staining evidenced the expression of immunoreactive IL-6 by hyperplastic ATII cells in fibrotic human lung, a condition in which alveolar macrophages are known to be activated. ATII cells in normal human lung did not express immunoreactive IL-6. Our findings demonstrate that ATII cells may be an important source of IL-6 in the alveolar space thereby participating to the regulation of the intra-alveolar immune response. Images